Study of The Concept of Vocational Guidance and Counseling in Vocational Schools - Linda Gea Vetrycia, Damai; Sukardi; Riki Mukhaiyar; Nurfarhanah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The concept of vocational guidance and counseling in vocational high schools (SMK) plays a crucial role in shaping the future of students. A recent study conducted at SMKS Teknologi YPL Lirik aimed to explore the general overview of guidance and counseling implementation, the steps taken by school principals and teachers, and the challenges faced in this aspect. Using a qualitative descriptive approach, the researchers directly collected data through interviews, documentation, and involving key stakeholders such as the school principal, vice principal of student affairs, subject teachers, class advisors, guidance counselors, and students. The gathered data was then analyzed through a process of reduction and interpreted qualitatively to draw conclusions. According to the interviews conducted with school officials, it was revealed that the current guidance and counseling practices at SMKS Teknologi YPL Lirik are inadequate. This is evident from the students' behavior, which tends to be naughty or undisciplined due to family or community environmental factors. To achieve holistic character education through guidance and counseling, the school must establish good cooperation with parents, maintain direct communication with them in case of any issues at school, and find solutions collaboratively to foster positive character growth in both the family and school environments. In conclusion, the study emphasizes the importance of enhancing guidance and counseling practices in vocational high schools to better support students in their personal and academic development. By addressing challenges and strengthening collaboration between school stakeholders, SMKS Teknologi YPL Lirik can create a more conducive environment for students to thrive and succeed in their vocational endeavors.